Determination of Mg concentration and distribution in MgxZn1−xO films for photonic devices application1. (2nd April 2014) - Ferlito, E. P.; Ricciari, R.; Padalino, M.; Grasso, S.; Battaglia, A.; Sciuto, M.; Mello, D.; Tapfer, L.; Gerardi, C.; Abel, Marie‐Laure; Rossi, Antonella; Watts, John F.
<x xml:space="preserve">Abstract</x> Among the transparent conductor, one of the most interesting is the Al doped MgxZn1−xO films for their electrical properties that make it very attracting for solar cell application. In this work, the Mg distribution in Al doped MgxZn1−xO films was investigated in order to find a reliable methods to determine Mg distribution. In particular, X‐ray diffraction, Auger electron spectroscopy and time of flight secondary ion mass spectrometry were used to characterize the film. Time of flight secondary ion mass spectrometry MCs+ results appear to be the most promising analytical technique. Copyright © 2014 John Wiley & Sons, Ltd.